Histórias de Pescadores: estudo com ribeirinhos desalojados por uma hidrelétrica - Duarte-Alves, Andréia; Justo, José Sterza [UNESP] (My University, 2011)
In this research, made with riparians ousted by the construction of an hydroelectric power station, were gathered histories of the time when they were living in the edges of the river and of the current life in the town constructed in substitution to the ancient village flooded by the dam. In the histories, they proliferate images of a time of abundance, of fishing and of the fertile land that they were cultivating on the edge of the river. They describe the old village, with wealth of details, their achievements in the fishing and in the challenge of the mysteries of the forest and of the ferocity of the wild animals. They talk about the daily life of the ancient village like a community in which they were near and supportive. In the current narratives the protest and the revolt remain against the construction of the hydroelectric power station that took away the river and the rich riverside life, placing them at a place that they find sterile and devitalized.

En su encuesta de ribereños desplazadas por la construcción de una central hidroeléctrica, se recogieron historias de la época que habitaban las orillas del río y la vida actual en la ciudad construida para reemplazar el antiguo pueblo inundados por la presa. En las muchas historias que contar, la proliferación de imágenes de una época de abundancia, la pesca y la abundancia de tierras fértiles que creció a lo largo de la orilla del río. Describir el casco antiguo, con detalles ricos, e informar con entusiasmo, su destreza en la pesca y frente a los misterios de la selva y la ferocidad de los animales salvajes. Hablan todos los días de la antigua ciudad como una comunidad en la que todos estaban cerca y de apoyo. En las narraciones siguen siendo actuales protesta y la rebelión contra la construcción de la presa que se llevó el río y la vida del río rico, colocarlos en un lugar que consideran estéril y sin vida.

Nesta pesquisa, realizada com ribeirinhos desalojados pela construção de uma hidrelétrica, foram recolhidas histórias do tempo em que habitavam as margens do rio e da vida atual na vila construída em substituição ao antigo povoado alagado pela barragem. Nas tantas histórias que contam, proliferam imagens de um tempo de fartura, de pesca abundante e da terra fértil que cultivavam à beira do rio. Descrevem a antiga vila, com riqueza de detalhes, e relatam, com entusiasmo, suas proezas na pesca e no enfrentamento dos mistérios da mata e da ferocidade dos bichos selvagens. Falam do cotidiano da antiga vila como uma comunidade na qual todos eram próximos e solidários. Nas narrativas atuais restam o protesto e a revolta contra a construção da hidrelétrica que lhes retirou o rio e a rica vida ribeirinha, colocando-os num lugar que consideram estéril e desvitalizado.
Fishermen's histories: a study with riparians ousted by a hydroelectric power station
Historias de pescadores: un estudio con los ribereños desalojados por una central hidroeléctrica
Keywords: Fishermen; Histories; Riparians; Memory; Daily life; Pescadores; Historias; Ríos; Esmemoria; Cotidiano; Pescadores; Histórias; Ribeirinhos; Memória; Cotidiano